Locally developed electronic trauma registry: a novel solution for low-income settings. (1st March 2011) - Mehmood, A; Razzak, J A; Raza, S; Mumtaz, N; Ejaz, K
Abstract : Introduction: A functionally active and well organised electronic trauma registry (ETR) can assist in addressing important issues about the prevention and treatment of injuries at hospital and regional level. The ideal process of development of such a registry includes its customisation according to the local needs and enabling the end users to give their feedback to the software programmers who can improvise it accordingly. Examples of ETRs in low and middle income countries are rare, mainly due to cost of obtaining and maintaining such registries. This prompted us for development of a local registry with the help of software programmers at a low cost with a user friendly interface. Attributes: The ETR uses both hardware and software to collect, verify, store and analyse the data. Effective coding systems for example, International Classification of Diseases (ICD-9-CM) and Abbreviated Injury Scaling (AIS) aid in standardisation of the terms, whereas backend spreadsheets and calculators help in storage, collation and analysis of the data. Scope: Information about patient demographics, injury location, injury date and time, external causes of injury, injury modifiers, mode of transport, ED/hospital assessment and treatment, final diagnosis, disposition and outcome can be recorded. The registry is capable of generating different trauma scores (GCS, RTS, ISS) and probability of survival (TRISS) score. Advantages: The registry could be used for hospital based injury surveillance, trauma outcome research and public policy interventions. When applied in multiple hospitals, it will serve as a city-wide trauma data bank.